Internet through the Eyes of 11-year-Old Children: First-Hand Experiences from the Technological Environment Children Live In - Kukkonen, Harri; Kurki, Heli (Human Technology, 2009)
The aim of this research is to obtain a deeper understanding of children’s own views and experiences of using the Internet, and their attitudes towards parental supervision and the technological environment in which they are growing up. This article reports on a survey of Internet use among the fifth-grade pupils in ordinary Finnish schools. The population studied was a selected sample, and the data were analyzed both statistically and by qualitative methods. Nine out of ten children are regular Internet users, and every second child uses the Internet daily. The contemporary Internet seems to be a means for social interaction for girls and for playing games for boys. In more general terms, the Internet serves as a different kind of information vehicle, depending on the user.